The H3.3 chaperone Hira complex orchestrates oocyte developmental competence - Smith, Rowena; Susor, Andrej; Ming, Hao; Tait, Janet; Conti, Marco; Jiang, Zongliang; Lin, Chih-Jen (Development (Cambridge, England), 2022)
Successful reproduction requires an oocyte competent to sustain early embryo development. By the end of oogenesis, the oocyte has entered a transcriptionally silenced state, the mechanisms and significance of which remain poorly understood. Histone H3.3, a histone H3 variant, has unique cell cycle-independent functions in chromatin structure and gene expression. Here, we have characterised the H3.3 chaperone Hira/Cabin1/Ubn1 complex, showing that loss of function of any of these subunits causes early embryogenesis failure in mouse. Transcriptome and nascent RNA analyses revealed that transcription is aberrantly silenced in mutant oocytes. Histone marks, including H3K4me3 and H3K9me3, are reduced and chromatin accessibility is impaired in Hira/Cabin1 mutants. Misregulated genes in mutant oocytes include Zscan4d, a two-cell specific gene involved in zygote genome activation. Overexpression of Zscan4 in the oocyte partially recapitulates the phenotypes of Hira mutants and Zscan4 knockdown in Cabin1 mutant oocytes partially restored their developmental potential, illustrating that temporal and spatial expression of Zscan4 is fine-tuned at the oocyte-to-embryo transition. Thus, the H3.3 chaperone Hira complex has a maternal effect function in oocyte developmental competence and embryogenesis, through modulating chromatin condensation and transcriptional quiescence.
Keywords: Animals; myši transgenní; Female; Oogenesis; transkripční faktory; Adaptor Proteins, Signal Transducing; oogeneze; Mice, Transgenic; ženské pohlaví; Chromatin; adaptorové proteiny signální transdukční; Zygote; Oocytes; zygota; Competent oocyte; Zygotic genome activation; Gene Knockdown Techniques; Mice; oocyty; Transcription Factors; signální transdukce; Histone H3.3; myši; Signal Transduction; Cell Cycle Proteins; Male; Hira complex; Embryonic Development; chromatin; genový knockdown; histony; Histones; zvířata; embryonální vývoj; mužské pohlaví; Mice, Inbred C57BL; proteiny buněčného cyklu; Histone Chaperones; Oocyte-to-embryo transition; histonové chaperony; myši inbrední C57BL